LACK Gene’s Immune Response Induced by Cocktail DNA Vaccine with IL-12 Gene Against Cutaneous Leishmaniasis in BALB/c Mice - Jorjani, Oghlniaz (Avicenna J Med Biotechnol, 2018)
BACKGROUND: Leishmaniasis is caused by parasitic protozoa of the genus Leishmania which is an obligate intracellular parasite in the infected host. Individuals who have been recovered from clinical leishmaniasis develop strong immunity against reinfection. DNA vaccines are the new type of vaccines that induce expression of protein eukaryotic cells. DNA vaccines can be stimulated by the cellular and humoral immune responses using one or several genes. METHODS: A DNA vaccine containing plasmids encoding the pcLACK+pcTSA genes of Leishmania major (L. major) (MHRO/IR/75/ER) in the vicinity of IL-12 gene expression was made and then its protective efficacy in comparison with single-gene of LACK was evaluated. Also, BALB/c mice were immunized intramuscularly three times. The humoral and cellular immune responses were evaluated after immunization with pcLACK, pcLACK+pcTSA+pCAGGS-IL12, and then challenged with L. major. RESULTS: Humoral response and IFN-γ values were significantly higher than control groups after immunization with pcLACK, pcLACK+pcTSA+pCAGGS-IL12 and challenge with L. major (p≤0.05). IL-4 values were increased in the control groups in such a way that they were remarkably higher than the pcLACK, pcLACK+pcTSA+ pCAGGS-IL12 groups (p≤0.05) after immunization and challenge with L. major. CONCLUSION: The survival time of the immunized mice with pcLACK, pcLACK+pcTSA+ pCAGGS-IL12 groups was higher than the control groups. Then, DNA vaccine of pcLACK appeared to be likely able to induce more protection against infection with L. major in mice. Therefore, cocktail DNA is effective to enhance specific immunity.